Recovery of lipase inhibitory compound from Aquilaria Malaccensis and Subintegra matured leaves extract via pretreatment using bath sonicator: effect of time - Mashuri, Nurul Farhana (2017)
Obesity has been arising from a day to day and has become a very complicated health issue worldwide that must be seriously taken. Obesity can be prevented by inhibiting pancreatic lipase that will block adsorption of fat. Aquilaria spp. (gaharu) is one of Malaysian treasures, rich in phytochemicals content in its resin. It was attentive to discover the miracle of this species which having a lot of health benefits including as a natural anti-obesity potent. This research was conducted to identify the effect of particle size on the inhibition activity at different ultrasonic time reaction. It was also carried out to determine the inhibitory effects of phytochemical compounds on pancreatic lipase that lead to the obesity prevention. The presence of phytochemical contents of both A.malaccensis and A.subintegra were observed. While the inhibitory effects on pancreatic lipase was examined using spectrophotometer analysis. The presence of phenolic and flavonoid compound in A. Malaccensis and A.Subintegra leaves extract. The parameters involved in the process were compound particle size of (0.25M, 0.5M, 1.0mM) and reaction time (30, 60, 90, 120 and 150 minutes) during inhibition of pancreatic lipase process. From the result obtained from using Mastersizer 2000E, the effect of ultrasonic reaction time on particle sizes are obtained which indicates the reduction of particle sizes across time. Next, inhibitory activity is determined by studying the effect of ultrasonic reaction on pancreatic inhibition activity. By getting those result, a new findings are obtains, which is the effect of particle sizes on inhibitory activities. The percentage of inhibition was higher at 90 minutes at the optimum temperature of 60 °C.